2020
DOI: 10.1097/tp.0000000000002872
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Mobile Health Intervention on Long-term Nonadherence After Lung Transplantation: Follow-up After a Randomized Controlled Trial

Abstract: Background. In a randomized controlled trial, lung transplant recipients (LTRs) using a mobile health intervention, Pocket Personal Assistant for Tracking Health (Pocket PATH), showed better adherence to the medical regimen than LTRs receiving usual care during the first year posttransplant. We examined whether these effects were maintained beyond the end of the trial and evaluated other potential risk factors for long-term nonadherence. Methods. Adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 73 publications
0
49
0
8
Order By: Relevance
“…The importance of patient engagement in mobile health intervention was also shown in a long-term follow-up study [35] of a recent randomized controlled trial evaluating the PocketPATH mobile app, which was designed to promote self-management for lung transplantation patients [36]. Despite a significant increase in short-term self-management behavior in the original study, there was no significant difference in most nonadherence elements in the follow-up study [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of patient engagement in mobile health intervention was also shown in a long-term follow-up study [35] of a recent randomized controlled trial evaluating the PocketPATH mobile app, which was designed to promote self-management for lung transplantation patients [36]. Despite a significant increase in short-term self-management behavior in the original study, there was no significant difference in most nonadherence elements in the follow-up study [35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a significant increase in short-term self-management behavior in the original study, there was no significant difference in most nonadherence elements in the follow-up study [35]. The authors speculated that the lack of sustained effect is likely to be related to a high rate of discontinuation of app use [35].…”
Section: Discussionmentioning
confidence: 99%
“…Good adherence to home monitoring after lung transplantation is associated with better patient and graft survival; however, previous studies have shown that adherence decreases over time [ 4 , 6 , 14 , 15 ]. Although this could not be directly evaluated with our current study design, it is likely that patient adherence to home spirometry increases with the online monitoring of home measurements by the transplant team.…”
Section: Discussionmentioning
confidence: 99%
“…The patients evaluated a new online home monitoring application and provided suggestions for improvement to specifically tailor the application for lung transplant recipients. As also suggested by Geramita et al, an application specifically designed for, and adapted with input from, lung transplant recipients could possibly improve long-term adherence and enable personalized treatment for individual patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] Recent studies in kidney and lung transplantation have accomplished variable success rates. [53][54][55] It is important to evaluate these novel technological applications not on a level of hardware performance (which is an implicated prerequisite), but firstly on their value for improving: medication adherence and adherence in general, a healthy life style and support of patients to achieve better self-management and self-care agency. Secondly, taking into account the costs and resources associated with these technologies, convincing and relevant improvements in…”
Section: ) Electronic Monitoring Systems Electronic Reminder or Alerting Systems Telemedicinementioning
confidence: 99%